Rancang Bangun Sistem Monitoring dan Pengisian otomatis Water Level Coolant Radiator Generator Kapal Berbasis IoT - Andi Zidane Ramadhan; Sri Mulyanto Herlambang; Sigit Purwanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The condition of the ship's generator coolant is always monitored because it affects the performance of the ship's engine. Maintaining the engine coolant temperature is very important to avoid damage that occurs because the engine coolant is too hot on the engine components. With the internet of things, a technological concept has the ability to connect and facilitate the communication process between machines, devices, sensors and humans via the internet network. The aim of this research is none other than to monitor and automatically fill the water level of coolant radiators on generator engines on ships using an IoT system. This research uses a prototyping method system. After designing the tool, testing the tool, monitoring system and automatic filling of the water coolant radiator on the generator engine, the average error rate in the ultrasonic sensor readings when the first test was carried out was 3.02%, the second error was 2.57%, and the third error was 3.63%. Meanwhile, the coolant water discharge data is known to be 3 seconds to 10 seconds with a discharge of 60.7 mL/s. Where this data is monitored on the Blynk 64 mL/s application with an error rate of 5.43%. Therefore, the monitoring and charging system for this water coolant radiator using the IoT system can work well.